2016
DOI: 10.3390/s16030395
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Haptic and Gesture Sensors for Rehabilitation of Bimanual Coordination and Dexterous Manipulation

Abstract: Disabilities after neural injury, such as stroke, bring tremendous burden to patients, families and society. Besides the conventional constrained-induced training with a paretic arm, bilateral rehabilitation training involves both the ipsilateral and contralateral sides of the neural injury, fitting well with the fact that both arms are needed in common activities of daily living (ADLs), and can promote good functional recovery. In this work, the fusion of a gesture sensor and a haptic sensor with force feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…Besides, others studies integrate support devices in addition to the LMC to assist the patient. In [ 27 ], the fusion of the LMC and the Omega.7 haptic sensor with force feedback capabilities has enabled a bilateral rehabilitation training therapy. The LMC tracks the healthy hand and the Omega.7 device haptically interacts with the impaired hand.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, others studies integrate support devices in addition to the LMC to assist the patient. In [ 27 ], the fusion of the LMC and the Omega.7 haptic sensor with force feedback capabilities has enabled a bilateral rehabilitation training therapy. The LMC tracks the healthy hand and the Omega.7 device haptically interacts with the impaired hand.…”
Section: Related Workmentioning
confidence: 99%
“…However, the GR mirror therapy group is required because of the accuracy and speed to perform tasks in program configuration [19]. A previous study reported an improvement in coordination, dexterity, hand use ability, and grasp force using a Leap motion controller with stroke patients [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…These GR algorithms mainly focus on the movement of arm, hands, eyes, legs, and other body parts. The main idea is to capture body movements using capture devices and send the acquired data to a computer [12]. A remarkable example is shown in physical rehabilitation, where the low-cost hardware and algorithms accomplish outstanding results in therapy of patients with mobility issues.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it needs to modulate the F I G U R E 8 Tele-rehabilitation by multimodal teleoperation adapted from ref. [127]. (a) The Leap Motion sensor tracks the motion of a healthy hand.…”
Section: Skill Generalisationmentioning
confidence: 99%